Wildfires on Cr-rich Ferralsols can cause freshwater Cr(VI) pollution: A pilot study in New Caledonia. (January 2023) - Thery, Gaël; Juillot, Farid; Meyer, Michael; Quiniou, Thomas; David, Magali; Jourand, Philippe; Ducousso, Marc; Fritsch, Emmanuel
Abstract: In the context of global warming, environmental forcing of wildfires on continental ecosystems is on a growing trend. Among other environmental impacts, wildfires can enhance trace metals concentration in freshwater systems. In this regard, chromium is of particular environmental and health concern because the temperature-induced oxidation of the less mobile and toxic Cr(III) form to the most mobile and toxic Cr(VI) one might represent a risk of freshwater pollution. The aim of the present study was to make a first assessment of this risk in New Caledonia by quantifying the influence of soil heating on Cr(VI) mobility in Cr-rich Ferralsols that cover about 1/3 of this French overseas territory. The results obtained indicated an enhanced Cr(VI) mobility upon soil heating from 200 °C, with a marked turnaround from 400 °C. Based on these results, a solid/solution mass balance approach allowed to confirm the risk of freshwater Cr(VI) pollution as a function of suspended particulate matter (SPM) concentration issued from burned Cr-rich Ferralsols. In addition, the results obtained revealed an apparent control of the Fe-oxides/silicates ratio on Cr(VI) mobility upon soil heating. Since this ratio decreases from the top to the bottom of ultramafic catchments, this latter result suggests that the risk of freshwater Cr(VI) pollution could depend on the actual location of the wildfires at the top or slope/base of these catchments. Since freshwaters represent the major water resource for the inhabitants of New Caledonia, these results point to the need for a larger evaluation of the risk of wildfires-induced freshwater Cr(VI) pollution at other catchments composed of Cr-bearing soils like Cambisols and Vertisols. At the larger scale, they also point to the need to foster studies aimed at better evaluating the risk of wildfires-induced freshwater Cr(VI) pollution at Cr-bearing pedological settings worldwide. Highlights: Heating of Cr-rich Ferralsols can result in a significant increase of mobile chromium. About 80% of mobile chromium after Cr-rich Ferralsols heating occurs as Cr(VI). The Fe-oxides/silicates ratio seems to control Cr(VI) mobility upon soil heating. Cr(VI) concentration in ultramafic freshwaters can exceed WHO GDWQ after wildfires. Risk of wildfires-induced freshwater Cr(VI) pollution should be assessed worldwide.